The Analysis of Factors Affecting Fertility in Riau Province in 2010-2017 - Restu Media; Tri Sukirno Putro; Rosyetti Rosyetti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Demographic transition refers to the declining of birth and death rates and is followed by a reduction in population growth rates. This demographic change is caused by demographic factors (birth, death and migration) and non-demographic factors (social and economic). Fertility is an important factor in population control which refers to the demographic transition. As fertility in control, it is expected to solve population problems. Riau Province has a relatively low rate of fertility reduction from other provinces in Sumatra. This study aims to look at the effect of per capita GRDP, the number of working women and poverty on fertility in regencies / cities in Riau Province. This study uses secondary data with data from 12 districts / cities in Riau Province in 2010 - 2017. This study has independent variables namely per capita GRDP, the number of working women and the number of poverty people. The analysis technique used is panel data regression which is a combination of time series data and cross section. Based on the results of research carried out per capita GRDP, the numbers of working women and poverty together have a significant effect on fertility in Riau Province. And partially per capita GRDP and the number of working women have a significant effect on fertility in Riau Province. This shows that in fertility control, these factors need to be included in fertility control in Riau Province.